Intrapulmonary concentrations of meropenem administered by continuous infusion in critically ill patients with nosocomial pneumonia: a randomized pharmacokinetic trial - Benítez-Cano, Adela (Crit Care, 2020)
BACKGROUND: Optimal antimicrobial drug exposure in the lung is required for successful treatment outcomes for nosocomial pneumonia. Little is known about the intrapulmonary pharmacokinetics (PK) of meropenem when administered by continuous infusion (CI). The aim of this study was to evaluate the PK of two dosages of meropenem (3 g vs 6 g/day by CI) in the plasma and epithelial lining fluid (ELF) in critically ill patients with nosocomial pneumonia. METHODS: Thirty-one patients (81% male, median (IQR) age 72 (22) years) were enrolled in a prospective, randomized, clinical trial. Sixteen patients received 1 g/8 h and 15 2 g/8 h by CI (8 h infusion). Plasma and ELF meropenem concentrations were modeled using a population methodology, and Monte Carlo simulations were performed to estimate the probability of attaining (PTA) a free ELF concentration of 50% of time above MIC (50% fT>MIC), which results in logarithmic killing and the suppression of resistance in experimental models of pneumonia. RESULTS: The median (IQR) of meropenem AUC(0–24 h) in the plasma and ELF was 287.6 (190.2) and 84.1 (78.8) mg h/L in the 1 g/8 h group vs 448.1 (231.8) and 163.0 (201.8) mg h/L in the 2 g/8 h group, respectively. The penetration ratio was approximately 30% and was comparable between the dosage groups. In the Monte Carlo simulations, only the highest approved dose of meropenem of 2 g/8 h by CI allowed to achieve an optimal PTA for all isolates with a MIC < 4 mg/L. CONCLUSIONS: An increase in the dose of meropenem administered by CI achieved a higher exposure in the plasma and ELF. The use of the highest licensed dose of 6 g/day may be necessary to achieve an optimal coverage in ELF for all susceptible isolates (MIC ≤ 2 mg/L) in patients with conserved renal function. An alternative therapy should be considered when the presence of microorganisms with a MIC greater than 2 mg/L is suspected. TRIAL REGISTRATION: The trial was registered in the European Union Drug Regulating Authorities Clinical Trials Database (EudraCT-no. 2016-002796-10). Registered on 27 December 2016.